2009
DOI: 10.1111/j.1469-7580.2009.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelin basic protein‐positive nerve fibres in human Meissner corpuscles

Abstract: Myelinated nerve fibres forming sensory corpuscles become amyelinic before entering the corpuscle. Interestingly, in Meissner corpuscles from monkey myelin basic protein (MBP), a specific component of myelin sheath co-localized with neuronal markers. To investigate whether or not this also occurs in human digital Meissner corpuscles, we used single and double immunohistochemistry to detect MBP associated with axonic (protein gene product (PGP) 9.5) or Schwann and Schwann-related cell (S100 protein) markers. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…It is generally accepted that Schwann cells lose the ability to myelinate as axons enter the receptor corpuscle; however, recent studies in human18 and primate digits19 report MBP immunoreactivity within the corpuscle. Approximately 25% of the MCs from human digital skin contained MBP‐immunoreactive nerve endings 10. Even so, they rarely appear to reach the apex of the papillae and purportedly do not actually supply the corpuscle.…”
Section: Cutaneous Neuroanatomymentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that Schwann cells lose the ability to myelinate as axons enter the receptor corpuscle; however, recent studies in human18 and primate digits19 report MBP immunoreactivity within the corpuscle. Approximately 25% of the MCs from human digital skin contained MBP‐immunoreactive nerve endings 10. Even so, they rarely appear to reach the apex of the papillae and purportedly do not actually supply the corpuscle.…”
Section: Cutaneous Neuroanatomymentioning
confidence: 99%
“…In comparison, cutaneous myelinated fibers have been much less explored, although numerous neuropathies are known to involve such distal myelinated nerve fibers. Recent studies have begun evaluating dermal myelinated fibers from glabrous skin with a variety of methods in healthy control populations9–11 and in patients with peripheral neuropathies 12–16. In this review, we will discuss the development of skin biopsy for investigation of normal and diseased dermal myelinated nerves.…”
mentioning
confidence: 99%
“…Previous studies have reported several SC-specific markers, and the most commonly used are S100 [ 2 ], MBP [ 1 , 3 ], MPZ [ 4 , 5 ], P75 NTR [ 6 , 7 ], GFAP [ 6 , 8 ], NCAM [ 5 , 9 ], GAP43 [ 6 , 10 ], PMP22 [ 11 ], Sox10 [ 12 ], Oct6 [ 13 ], O4 [ 14 ], Krox20 [ 15 ] and Sox2 [ 5 ]. Among them, S100 and P75 NTR are the most frequently used markers for the identification of stem cell—derived Schwann cell—like cells [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that Sox10 may be the only known marker constitutively expressed in the whole SC development process [ 19 , 23 ], while S100, the widely used SC marker, is not expressed in SCPs [ 24 ]. In addition, when iSCs differentiate into mSCs, transcription factor Oct6 is first expressed in pro-mSCs, inducing the expression of downstream transcription factor Krox20, which in turn regulates the expression of myelin-associated genes MBP and MPZ [ 3 , 10 , 15 , 25 27 ]. Another study suggested that Sox2, the marker for undifferentiated stem cells, is only expressed in SCPs and iSCs [ 5 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two mechanisms – growth along the endoneurial tube and direct axon growth – might be responsible for the regeneration of Meissner’s corpuscles. The process of regenerated Meissner’s corpuscle development includes the growth of axons inside the end of corpuscles along the endoneurial tube or repeated sprouting, being packaged by theca cells, and development into the corpuscle body [22,23]. At the early stage, the axons at the terminal part of Meissner’s corpuscles were un-myelinated.…”
Section: Discussionmentioning
confidence: 99%